Introduction to business statistics : - Kvanli, Alan H. (South-Western, 2000)
This book stresses data analysis, graphical interpretation, and decision making. The authors provide a clear understanding of the concepts and applications of statistics, hile giving students the opportunity to observe and actually carry-out computer generated solutions using Microsoft Excel and Minitab.